Roles of the Main Physical Properties of the Wet Granulation Product of Hawthorn leaf Extract Mixtures in High Shear Granulation. Issue 4 (1st August 2016) - Li, Zhe; Luo, Juan; Jiang, Qieying; Zhao, Guowei; Liao, Zhenggen; Liang, Xinli; Zeng, Ronggui; Lv, Dan
Abstract: The purpose of this study was to establish a relationship between the physical properties of powders and their behavior during high shear granulation. Hawthorn leaf extract was utilized as a model drug, and microcrystalline cellulose (MCC) and soluble starch were selected as excipients. The extract was mixed with each of the different excipients at ratios of 1:0.5, 1:1 and 1:2 by weight. The granules were prepared by high shear granulation (HSG). The wet granulated product was evaluated by monitoring responses such as the granule yield, the ratio of lumps to fine powder, the angle of repose of the granules (granule‐AOR) and the Hausner ratio of the granules (granule‐HR). The effect of the powder's physical properties on the granulation behavior was analyzed through stepwise regression. The critical relative humidity, particle size (d50), surface free energy, AOR, moisture content, equilibrium hygroscopic moisture content ( f ), specific surface area, pore volume, Carr index, contact angle with water and bulk density were the main factors linked to the granule product. The main physical properties of the extract powder were the important factors in HSG. The findings from this study are useful in preparing ideal granulation products by reasonably controlling the physical properties of powders. Practical Applications: The present work investigated the influence of the physical properties of Hawthorn leaf extract on high shear granulation behavior. Results showed that critical relative humidity, particle size, surface free energy, angle of repose, moisture content, equilibrium hygroscopic moisture content, specific surface area, pore volume, Carr index, contact angle with water and bulk density were the main factors linked to the granule product. Taking into consideration that the food industry uses Hawthorn leaf extract not only to plant health product as nutrient supplement but to botanical drug in several countries, this work is a useful guide to prepare ideal granulation products by reasonably controlling the physical properties of powders.